ANALISIS HUKUM TERHADAP PERLINDUNGAN PEREMPPUAN DALAN PERCERAIAN MENURUT AL-QUR’AN DAN HUKUM ISLAM - Ramadhani, Windi; ., Yanuardin; Siagian, Nilasari (UIN Sumatera Utara Medan, 2023)
Divorce is a complex social issue with significant implications, especially for women, within Islamic jurisprudence. Governed by the Quran and Islamic legal traditions, this research explores key questions: What protections does the Quran provide for women's rights during divorce? How does Islamic law interpret and enforce these protections. The study utilizes qualitative methods such as library research and field observation for comprehensive data collection, processing, and analysis. It highlights the Quran's directives on safeguarding women's rights in divorce proceedings, emphasizing their intrinsic value as per Islamic principles. The research underscores the crucial role of Islamic jurisprudence in ensuring women's rights protection in divorce scenarios. It emphasizes understanding how Islamic law regulates and safeguards these rights, thereby revealing broader societal implications of these legal frameworks. Ultimately, the study advocates for a nuanced understanding of how Islamic teachings and legal traditions contribute to protecting and empowering women in the context of divorce, fostering a deeper appreciation of their rights within Islamic legal frameworks. Keywords: Protection, Women's Rights